PENGARUH KUALITAS PRODUK, KEPERCAYAAN KONSUMEN, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI CV. ANUGRAH KEDIRI - Arridho, Fadhel Ahmad; Suwarsono, Edy; Wardhani, Rike Kusuma (Commodities, Journal of Economic and Business, 2023)
This study aims to determine the effect of product quality, consumer confidence, and location on purchasing decisions at CV. Kediri's gift. The analytical tool used is multiple linear regression analysis with a significance level of <0.05. From the results of the analysis conducted, it shows that the three independent variables have no partial effect on the dependent variable, namely the product quality variable with a t value of -0.774 and a significance value of 0.444, which means that product quality does not have a partial effect on purchasing decisions. In the consumer trust variable with a t value of -0.731 and a significance value of 0.470, which means that consumer trust does not have a partial effect on purchasing decisions. The location variable has a t value of 1.116 and a significance value of 0.272, which means that location has no partial effect on purchasing decisions. Simultaneous test results show that the F value is 0.868 and the significance value is 0.466, which means product quality, consumer confidence, and location do not simultaneously influence purchasing decisions.